2007
DOI: 10.1177/000348940711600708
|View full text |Cite
|
Sign up to set email alerts
|

Mass Psychogenic Illness Presenting as Acute Stridor in an Adolescent Female Cohort

Abstract: Audible stridor can arise from numerous disease processes. In the vast majority of presentations it occurs sporadically and on an individual basis. Our cohort is especially unusual because of the sheer number of patients. Our presentation of a case of mass psychogenic illness as the cause of vocal cord dysfunction with additional findings of laryngomalacia within a group of adolescent girls is the first in the English-language literature. The key to the diagnosis is recognition of the disorder and susceptible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
13
0
4
Order By: Relevance
“…Although uncommon, PMDs may be patterned after psychogenic rather than organic disease, thereby precipitating outbreaks of psychogenic illness. This phenomenon, termed “mass hysteria,” classically occurs in the setting of war, but may also affect clusters of adolescent school girls 33, 34…”
Section: Discussionmentioning
confidence: 99%
“…Although uncommon, PMDs may be patterned after psychogenic rather than organic disease, thereby precipitating outbreaks of psychogenic illness. This phenomenon, termed “mass hysteria,” classically occurs in the setting of war, but may also affect clusters of adolescent school girls 33, 34…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by the terms initially used to describe the condition, such as hysterical stridor, factitious asthma, and Munchausen stridor, many investigators have postulated that PVFM might be caused by psychological stress, anxiety, trauma, hysteria, or other psychiatric conditions. A number of studies have reported a high prevalence of these types of conditions in their sample [22-28] but other investigators have not, and some authors have argued that the higher rates of anxiety and depression that have been described may be the effect rather than the cause of PVFM [13, 29, 30]. There are clearly some individuals in whom counseling alone or in conjunction with speech therapy can produce a resolution of symptoms [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have reported successful outcomes after 1 session [9, 10], others report that the treatment course for some individuals may often last for 4 sessions or more [19, 28, 32-38]. There is also some evidence that, for some adults with PVFM, multiple treatment sessions over a longer time period may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Stridor may result from neoplasms, such as Hodgkin's disease and thyroid masses. Myasthenia gravis may occasionally be associated with stridor [1].…”
Section: Discussionmentioning
confidence: 99%